Relationship between hyperferritinemia and clinical manifestations of gout - H. P. Kuzmina; O. M. Lazarenko (Zaporožskij Medicinskij Žurnal)
Aim. To study the parameters of ferritin, uric acid in the serum and urine, high-sensitivity C-reactive protein (hsCRP) in patients with hypertension in combination with gout and the relationship between these data and clinical manifestations of gout.